Impact of pathogenic fungi, herbivores and predators on secondary succession of tropical rainforest vegetation. (6th March 2020) - Szefer, Piotr; Molem, Kenneth; Sau, Austin; Novotny, Vojtech
Abstract: There is growing evidence that top–down biotic factors play an important role in plant community dynamics and are able to maintain the high plant diversity of primary tropical forests. However, the top–down impact by herbivores on the accumulation of plant biomass, richness and the community assembly process remains poorly known for the initial stages of secondary ecological succession. Here we test the top–down effects of natural enemies on the biomass, richness, diversity, community composition, trait dynamics and randomness during the assembly process on an early successional community in a lowland tropical forest in Papua New Guinea. We initiated secondary succession on 36 vegetation plots (5 × 5 m) organized in six blocks. After 1 year we evaluated successional community characteristics in each block containing a control plot and five treatment plots: experimentally excluding (a) insects by insecticides, (b) fungal pathogens by fungicides, (c) vertebrate predators and ants with exclosures and traps and experimentally adding (d) low and (e) high levels of a generalist herbivore species. Insects were responsible for increased plant diversity, shifts in plant community composition and a decrease in community weighted mean of leaf dry matter content. The lack of herbivores resulted in a diversifying effect but did not affect plant biomass and stem density. No other treatment had a significant effect on plant diversity during succession. The highest level of artificially increased herbivore density reduced plant biomass, while the fungicide treatment decreased stem density of woody plants. Using a null model approach, we showed that the removal of insects and their vertebrate predators increased randomness during the community assembly processes for woody plants, whilst the same effect was not found for the removal of fungi or elevated herbivore abundances. Synthesis . Early rainforest succession was not entirely plant driven. During the early succession of lowland tropical forest, insect herbivores enhanced plant diversity and caused shifts in community structure by promoting species with acquisitive leaf traits. As expected, the early successional communities were highly variable, but insects and vertebrate predators reduced randomness during the assembly process. Insect and vertebrate communities can thus impact the regeneration dynamics of tropical forests. In contrast, fungal pathogens were less important in maintaining high diversity of successional communities in our system. Abstract : Early rainforest succession was not entirely plant driven. During the early succession of lowland tropical forest, insect herbivores enhanced plant diversity and caused shifts in community structure by promoting species with acquisitive leaf traits. As expected, the early successional communities were highly variable, but insects and vertebrate predators reduced randomness during the assembly process. Insect and vertebrate communities can thus impact the regeneration dynamics of tropical forests. In contrast, fungal pathogens were less important in maintaining high diversity of successional communities in our system.